RETRACTION : Increased Salivary Lipid Peroxidation in Human Subjects With Oral Lichen Planus (International journal of dental hygiene, 2025)
RETRACTION : F Agha‐Hosseini , I Mirzaii‐Dizgah , S Mikaili and M Abdollahi , “,” International Journal of Dental Hygiene 7 , no. ( 2009 ): 246 – 250 , https://doi.org/10.1111/j.1601‐5037.2009.00365.x . The above article, published online on 14 October 2009 in Wiley Online Library ( wileyonlinelibrary.com ), has been retracted by agreement between the journal Editor‐in‐Chief; and John Wiley & Sons Ltd. The retraction has been agreed upon following an investigation into concerns raised by a third party. The investigation revealed that the graphs shown in Figures 1a and 1b appear identical. However, the difference between the control and case group shown in Figure 1a is reported as statistically significant while the difference shown in Figure 1b is reported as not statistically significant. The authors responded to the concerns and provided data to support their results. However, the data did not meet the acceptable standards for raw data and also did not correspond with the graph shown in Figure 1b. As a result, the editors have lost confidence in the results and conclusions presented in this article.